Pengaruh Knowledge Sharing, Human Relation, dan Self Efficacy terhadap Kinerja Pegawai (Studi Kasus pada Badan Pengawasan Keuangan dan Pembangunan (BPKP) Perwakilan Provinsi Jawa Timur) - Umi Nafakhatu Ambariya; Sumartik Sumartik; Kumara Adji Kusuma (Ekonomis: Journal of Economics and Business, 2026)
The purpose of this study is to analyze the influence of knowledge sharing, human relations, and self-efficacy on the performance of BPKP East Java Representative employees. This type of research uses a quantitative approach with a survey method using a questionnaire to collect data. The sampling technique in this study used a total sampling of 190 employees. Multiple linear regression analysis includes classical assumption tests, validity tests, reliability tests, t-tests, F-tests and determinant coefficients. The results of this study reveal that simultaneously and partially there is a positive and significant influence between the variables of knowledge sharing, human relations, and self-efficacy on employee performance at the BPKP East Java Representative Office.